The Supervision of English Language Teachers in Public Secondary Schools in Kenya: A Critical Role of Heads of English Department - Barasa, Wakasa Diana; Onchera, Onsare Paul; Okari , Florence Mokeira (Journal of Education and Practice, 2022)
Purpose: The study assessed the role of heads of English department in the supervision of English language teachers in public secondary schools in Kakamega county, Kenya among other objectives. Supervision is key in enhancing learning-teaching experiences. In order to ensure better supervision of English language teachers, the heads of English department should play a key role in supervision. When their roles are not carried out efficiently, the teachers may not reach their full potential and learners may underperform. In Kenya, there is no official supervision approach that is exclusively used for supervising teachers of English in secondary schools, which means that teachers of English are not being effectively supervised, and this leads to negative impact on curriculum delivery. Methodology: This article is based on the research study done in Kakamega County, which explored English Language Teachers` opinions about the usefulness of Collaborative Peer Supervision (CPS) approach in enhancing Teacher Effectiveness in the teaching of English Language in public secondary schools in Kenya. The study adapted the Convergent Mixed Methods Research Design, where, 25 heads of English department were purposively sampled from the 417 public secondary schools in Kakamega county, and were interviewed using a researcher-developed in-depth interview schedule. Data collected was thematically analyzed using NVIVO12 Software. Findings: The results revealed that, the major supervisory roles of HODs currently, is administrative i.e., supervision of curriculum implementation at the departmental level, conducting teacher appraisals, and general management of departmental issues. This is formal supervision through the Teacher Performance Appraisal and Development (TPAD) tool, which is the current supervisory approach, recognized by the Teachers` Service Commission (TSC), the teachers` employer in Kenya. The study also revealed that HODs are not fully sensitized about other key supervisory roles that they should play, in accordance with the literature. The results were presented thematically, by way of verbatim quotes as expressed by the participants` responses, and researcher commentaries. Unique Contribution to theory, practice and policy: The study concluded that teachers of English in public secondary schools in Kenya, are not being effectively supervised because the HODs are not fully sensitized about their full supervisory roles. The study recommends the development of capacity building programs on supervisory roles for HODs through workshops and seminars, and the introduction of CPS as a complementary supervision approach for supervising teachers of English in secondary schools, in which HODs will take the centrality of guiding supervision in their departments. This should guarantee the delivery of high-quality instruction.